Complementary Feeding and the Nutritional Status of Children 6-23 Months Attending Kahawa West Public Health Center,Nairobi - Kimwele, Angelica; Ochola, Sophie (IOSR Journal of Nursing and Health Science (IOSR-JNHS, 2017)
A cross-sectional analytical study was carried out at the Kahawa West Public Health Centre , Nairobi, Kenya, among randomly sampled 286 mothers and their children aged 6-23 months. Data was entered and analyzed using (SPSS version 20). Anthropometric measurements were analyzed using ENA for SMART. Chi-square test (p< 0.05) was used to show the relationships. The respondents were mostly young (mean age 26.1±4.7 years), married (88.1%), housewives (66.4%) with mainly primary school level of education (47.2%). The main sources of income for most households were business (48.6%) and casual labour (31.8%). All (100%) the children aged 6-8 had been introduced to solids, semi-solids and soft foods. Majority of the breast-fed children received minimum meal frequency; 6-8 months old (95.9%) and 9-23 months old (96.4%) unlike the non-breast fed children (55.0%). The percentage of children who consumed vitamin A rich foods was 60.8% and iron-rich foods were 11.5%. Over three quarters (79.0%) of the children attained the minimum dietary diversity whereas 75.9% attained the minimum acceptable diet. Overall, 13.3% of all the children were stunted, 11.9% wasted and 16.8% underweight. Children who did not attain the minimum meal frequency were likely to be wasted (chi-square test; 0.001) and underweight (chi-square test; 0.013).Nutrition messages on Infant and Young Child Feeding Practices should emphasis dietary diversity and frequency of feeding especially for nonbreastfed children
Keywords: complementary feeding; minimum acceptable diet; minimum meal frequency; minimum dietary diversity